France - Fontes, Justine; Fontes, Ron. (New York : Children's Press, 2003)
Alphabetically arranged entries introduce children to various aspects of France, including its animals, people, landmarks, cuisine, and more.
Animals -- Buildings -- Cities -- Dress -- Exports -- Food -- Government -- History -- Important people -- Jobs -- Keepsakes -- Land -- Map -- Nation -- Only in France -- People -- Question -- Religion -- School & sports -- Transportation -- Unusual places -- Visiting the country -- Window to the past -- X-tra special things -- Yearly festivals -- Zeste.
Includes bibliographical references (p. 39) and index.
Kirkus Review.
6.0
K-3
Keywords: France -- Juvenile literature; France; France; France